Skills of Educational Managers in Private Higher Education Institutions in Addis Ababa City Administration - Teshome, Samson Worku; Woldegerima, Haileselassie (Darul Yasin Al Sys, 2025)
This study investigates the managerial competencies of educational managers in private higher education institutions within Addis Ababa City Administration, Ethiopia. Data were collected through structured questionnaires administered to both educational managers and teaching staff, focusing on core management skill areas including conceptual, interpersonal, technical, decision-making, problem-solving, and leadership abilities. Descriptive statistical tools—frequency counts, percentages, mean scores, and standard deviations—were employed to analyze the responses. The findings indicate that while interpersonal communication and relationship management are generally well-developed, critical skill gaps exist in areas such as delegation, staff motivation, forecasting, and analytical decision-making. These deficiencies highlight the need for structured professional development initiatives tailored to enhance managerial effectiveness and leadership capacity. The study emphasizes the strategic importance of equipping educational managers with a balanced and comprehensive skill set to foster institutional performance, improve governance practices, and support the professional growth of subordinates. This research contributes to the broader discourse on educational leadership by offering empirical insights into the current competency landscape of private higher education managers in Ethiopia and underscores the urgency of capacity-building interventions aligned with contemporary managerial demands.